PENGARUH KETERSEDIAAN AIR BERBEDA TERHADAP PERTUMBUHAN DAN HASIL TIGA KULTIVAR BAWANG MERAH (Allium cepa L.) - Nana Ariska; Diah Rachmawati (Jurnal Agrotek Lestari, 2018)
The availability of water is an important factor that greatly affects the growth and yield at the onions. The objective of this research was to study the growth content of three cultivars of onions (Allium cepa L.) on different water availability condition. This research was conducted in the Sawit Sari Greenhouse, Laboratory of Plant Physiology Faculty of Biology and the Laboratory of Chemistry, Faculty of MIPA, University Gadjah Mada in September-December 2015. The design used in this experiment was a Complete Random Design (CRD) with two factors, cultivar and frequency of watering. The cultivars used were Biru Lancor (V1), Crok Kuning (V2), Tiron (V3) using differences watering frequency: 2 times daily watering (P1), once a day watering (P2), once a watering in 2 days (P3), once a watering in 3 days (P4). Each treatment combination was done with 5 replication. Water treatment was done in second week until eight week after planting. The observed parameters included leaves length, number and fresh weight of the leaves, the length and weight of roots, fresh weight and dry weight of tubers which measured by digital scales and tape measure. Data were analyzed using Analysis of Variant (ANOVA). The results showed the differences in frequency of watering influences the growth, and yield content of three cultivars of onions. Leaves length, fresh weight, and number of leaves decreased with the reduction of the frequency of watering. Root length and fresh weight of root, fresh and dry weight of tuber increased with the reduction of the watering frequency. Keywords: Onion (Allium cepa L.), drought,